Longitudinal research on the dynamics and internal mechanism of female entrepreneurs’ passion - Fu, Xiaorong; Ran, Yaling; Xu, Qian; Chu, Tianshu (Frontiers in Psychology, 2022)
Based on Vallerand’s dualistic model of passion, this study theorizes and empirically examines the temporal dynamics of two types of entrepreneurial passion in female entrepreneurs – harmonious entrepreneurial passion (HmEP) and obsessive entrepreneurial passion (ObEP) – and examines the mechanisms by which entrepreneurial effort and fear of failure influence the temporal dynamics of entrepreneurial passion. Using data collected from a three-wave, lagged survey of female entrepreneurs, we employed Mplus to build a latent growth model for entrepreneurial passion and built a cross-lag model of the relationship between entrepreneurial passion, entrepreneurial effort and fear of failure. We found that female entrepreneurs’ HmEP and ObEP present different temporal dynamics. Furthermore, the temporal dynamics of HmEP are achieved through changes in entrepreneurial effort, whereas the temporal dynamics of ObEP are achieved through changes in current entrepreneurial effort and fear of failure in the next stage. Therefore, due to traditional gender stereotypes and varying motivations to engage in entrepreneurship, the two entrepreneurial passions have different dynamic evolution processes. Our results underscore the importance of effort and fear of failure in stimulating the dynamics of female entrepreneurial passion.